Implementasi Bimbingan Kelompok untuk Mengembangkan Sikap Altruisme Siswa SMP dalam Menghadapi Era Society 5.0 - Fahira, Ihza Chaidaratul; Kaesti, Mutiarani R. D. E; Aiwani, Aisyiah; Nate, Mahara Pinte; Hasanah, Binti Uswatun; Munir, Ah. Fahri (Prodi Bimbingan Konseling FKIP UNDANA, 2024)
Society 5.0 emphasizes the integration of technology into everyday life as a support system and enhancer of social welfare. Altruism, or the spirit of helping others, becomes a crucial component in this era, as adolescents, particularly junior high school students, are more focused on existing technologies, thus neglecting fundamental life values such as mutual aid, empathy, social engagement, and other life challenges. In this context, research on the implementation of group counseling to foster altruistic attitudes among junior high school students becomes relevant and essential. This study aims to explore the implementation of group counseling services to develop altruistic attitudes among junior high school students in the Society 5.0 era. Additionally, it underscores the importance of incorporating lessons on caring for and assisting others in the school curriculum. This proactive step helps children and teenagers prepare themselves to face new challenges in the Society 5.0 era. This paper utilizes the Study Library Research technique, incorporating both primary and secondary data sources such as textbooks, article titles, books, and relevant documents. Through the examination, it is concluded that Group Counseling can serve as a means to develop Altruistic Attitudes among junior high school students in the Society 5.0 era. In conclusion, this research highlights the relevance and urgency of implementing group counseling to cultivate altruism among junior high school students in the face of the Society 5.0 era. The practical implications of this research can serve as a foundation for educators and policymakers to enhance the effectiveness of holistic education prioritizing character and social values.